PENGARUH UPAH, LINGKUNGAN KERJA DAN STRES KERJA TERHADAP KINERJA PEGAWAI TIDAK TETAP (PTT) DI RSUD EMBUNG FATIMAH KOTA BATAM - Kalvin Rico Telaumbanua; Ade Parlaungan Nasution; Lukmanul Hakim (University of Riau Kepulauan, 2016)
In this study, the authors intend to answer a few basic ideas, so research to be answered through this research are : Are Wages influence on employee performance, Is Work Environment influence on employee performance, Is Work Stress influence on employee performance, and Do Wages, Work Environment and Job stress jointly influence on employee performance in RSUD Embung Fatimah Batam City.The results of this study indicated with tcount, that wages have a significant and positive effect on employee performance amounted to 3,133 1,294. The working environment has a positive and significant impact on employee performance amounted to 2,736 1,294. And job stress has a positive and significant impact on employee performance amounted to 3,399 1,294.Like wise with Wages, Work Environment and Stress work together-together have an influence on employee performance in Batam City Hospital Fatimah Embung indicated by the value of R 2 (R Square) of 0.841 or 84.1 %. This means the ability to variables Wages, Working Environment and Work Stress in explaining variable employee performance is 84.1 %, which means quite closely. The remaining 15.9% is explained by other variables not in this study.